MENINGKATKAN KESADARAN HIDUP SEHAT YANG SELARAS DENGAN MANAJEMEN BISNIS SYARIAH DI TENGAH PANDEMI COVID 19 DI DESA KARACAK, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Ujang Buchori Muslim; Hasbi Ash Shiddieqy; Endah Fitriani (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
Islamic economics and business, especially sharia business management, certainly requires the right environment for its application. In the midst of the Covid-19 pandemic that hit the world, sharia business management means little without awareness of healthy living. The application of Islamic economics and business and especially sharia business management cannot be carried out without an awareness of healthy living. In the community service activities carried out in Cengal Village, Karacak Village, Leuwiliang District, Bogor Regency, this was emphasized. Society understands that Islam is a perfect system of life. It includes economics, business and management. It also includes health, which in Islamic terms are interconnected and support each other as a system. Therefore, people's understanding, which already has this foundation, needs to always be strengthened, especially in the midst of the Covid-19 Pandemic. Through this community service activity the understanding of rural communities is increasing within the scope of Islamic harmony as a comprehensive view of life.